2017
DOI: 10.1089/neu.2016.4680
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Modulation as a Target for Ameliorating Effects of Blast Induced Traumatic Brain Injury

Abstract: Blast traumatic brain injury (bTBI) has been shown to contribute to progressive neurodegenerative disease. Recent evidence suggests that endoplasmic reticulum (ER) stress is a mechanistic link between acute neurotrauma and progressive tauopathy. We propose that ER stress contributes to extensive behavioral changes associated with a chronic traumatic encephalopathy (CTE)-like phenotype. Targeting ER stress is a promising option for the treatment of neurotrauma-related neurodegeneration, which warrants investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In a blast injury model of TBI, the number of apoptotic neurons and expression of apoptotic proteins were found to be significantly reduced in mice receiving the ER stress inhibitor salubrinal, also known as the eIF2α dephosphorylation inhibitor ( 190 ). Consistent with this observation, multiple studies reported that salubrinal confers neuroprotection by attenuating ER-stress-associated neuronal cell death and neuroinflammation after TBI ( 191 – 193 , 195 , 196 , 259 ). Concomitantly, the administration of low-dose guanabenz (an activator of eIF2α phosphorylation) to mice after TBI could reduce cortical and hippocampal tissue and neuron loss, which in turn could improve motor and cognitive functions ( 197 , 198 ).…”
Section: The Role Of Endoplasmic Reticulum Stress In Neurological Dis...supporting
confidence: 57%
“…In a blast injury model of TBI, the number of apoptotic neurons and expression of apoptotic proteins were found to be significantly reduced in mice receiving the ER stress inhibitor salubrinal, also known as the eIF2α dephosphorylation inhibitor ( 190 ). Consistent with this observation, multiple studies reported that salubrinal confers neuroprotection by attenuating ER-stress-associated neuronal cell death and neuroinflammation after TBI ( 191 – 193 , 195 , 196 , 259 ). Concomitantly, the administration of low-dose guanabenz (an activator of eIF2α phosphorylation) to mice after TBI could reduce cortical and hippocampal tissue and neuron loss, which in turn could improve motor and cognitive functions ( 197 , 198 ).…”
Section: The Role Of Endoplasmic Reticulum Stress In Neurological Dis...supporting
confidence: 57%
“…Altered tau processing has frequently been observed in experimental animal models of blast injury [ 2 , 4 , 5 , 11 , 13 , 17 , 22 , 23 , 35 , 39 , 43 , 44 , 52 , 57 , 58 , 61 63 , 67 , 70 , 73 , 83 , 86 , 88 ]. The blast-exposed rats studied here develop a variety of chronic and persistent PTSD-related behavioral traits [ 81 ] following repetitive low-level blast exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Statz et al ( 84 ), subjected rats to a repetitive mild blast TBI of 74.5 kPa over 3 consecutive days and found that a part of the blast cohort, but not all animals, manifested anxiety measured by elevated zero maze, light/dark emergence test and fear conditioning, 3 weeks and 6 months post blast impact ( 84 ). Increased anxiety behavior at 24 hrs to 3 days post blast exposure was observed in the open field test only when the animals were placed at the exit end of the blast tube or were subjected to multiple blast exposures over days ( 19 , 54 , 66 , 85 , 86 ). EPM and light /dark emergence tests showed long term deficits of anxiety following bTBI and may be more accurate tests for anxiety.…”
Section: Summary and Discussionmentioning
confidence: 99%